The effect of intellectual capital on corporate value - Rahayu, Yayuk Sri; Widiati, Putri Kurnia (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2018)
Economic development has many methods in development of financial institutions banking. Liquidity management can affect the institution. The crisis in financial sector is caused by low capability of financial institutions to deal fund sources. It affects the development of securities market and real sector. This study aims to analyze the effect of Intellectual Capital on Banking Value in Indonesia. The effect of Intellectual Capital is derived revenue (financial performance) on Banking Value, indirect effect of Intellectual Capital to Company's value of financial performance. This research is a descriptive explanatory research to test the hypotheses. The population is all Indonesia Banking. This research uses 30 banks with 5 years period (series) from year 2011 until 2015. The samples are 5 years x 30 = 150 item data and analyzed by path analysis. The research results indicate that companies should aware to important role of intellectual capital management. Company must manage intellectual capital within company, because it can affect on firm value. Intellectual capital has a significantly and positive effect on financial performance. In addition, there is an indirect effect of Intellectual Capital on firm value through financial performance. Optimal intellectual capital will create value added to company to provide a separate characteristic. The company will be able to compete with its competitors, because it has a unique competitive advantage.Keywords: intellectual capital, financial performance, corporate value